2021
DOI: 10.21037/atm-21-2906
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-induced UCK2 m6A hypermethylation promotes melanoma cancer cell metastasis via the WNT/β-catenin pathway

Abstract: Background: Melanoma is a highly aggressive, malignant skin tumor with a statistically high mortality rate. N6-methyladenosine (m 6 A) modification is involved in a variety of biological processes, including tumorigenesis. m 6 A modifications regulate the fate and functions of RNA, such as mRNA stability, nuclear processing, transport, localization, translation, primary microRNA (miRNA) processing, and RNA-protein interactions. Several members (including METTL3, METTL14, FTO, ALKBH5, and YTHDF2) are actively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Similarly, Dickkopf‐1 (DKK1) can reduce the osteogenic potential of BMSCs and cause bone loss 31,32 . Previous studies have shown that Mettl3 could regulate the Wnt/β‐catenin pathway 33,34 . However, the regulatory mechanism of Mettl3 influences the bone differentiation of OP‐BMSCs through the canonical Wnt pathway is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dickkopf‐1 (DKK1) can reduce the osteogenic potential of BMSCs and cause bone loss 31,32 . Previous studies have shown that Mettl3 could regulate the Wnt/β‐catenin pathway 33,34 . However, the regulatory mechanism of Mettl3 influences the bone differentiation of OP‐BMSCs through the canonical Wnt pathway is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al. found that UCK2 overexpression was regulated by m 6 A-METTL3 axis in melanoma metastasis ( 53 ); Chang et al. proposed that miR-302a-3p targets and suppresses the expression of METTL3 to inhibit melanoma cell progression ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role played by m6A in melanoma is not fully understood, and only a few research results have been reported. A study found that METTL3 induced UCK2 m6A hypermethylation and promoted the metastasis of melanoma cells through the WNT/β-catenin pathway [ 290 ]. METTL3 may be involved in the proliferation, invasion, migration and resistance of melanoma cells [ 291 , 292 ].…”
Section: M6a and Cancersmentioning
confidence: 99%